An update to the taxonomy of the genus Macroderes Westwood 1842 (Coleoptera: Scarabaeidae: Scarabaeinae) with descriptions of new species from South Africa - Abdalla, Ishtiag H.; Deschodt, Christian M.; Scholtz, Clarke H.; Sole, Catherine L. (Zootaxa, 2018)
The genus Macroderes Westwood, 1842 (Scarabaeidae: Scarabaeinae, tribe incertae sedis) is practically endemic to South Africa with only one species that is found little north in southern Namibia. The ranges of the species are limited to the winter-fall and bimodal biomes of South Africa comprising the regions of Richtersveld as extreme points of its northerly distribution, and extending to the south through Namaqualand to Cape Agulhas. The taxonomy of the genus is revised. Fourteen valid species are recognised and three others are of doubtful validity. Seven new species are described, these are: M. cederbergensis Abdalla & Deschodt, new species, M. tortuosus Abdalla & Scholtz, new species, M. gifboomi Abdalla & Scholtz, new species, M. leipoldti Abdalla & Deschodt, new species, M. oreatus Abdalla & Deschodt, new species, M. porselinus Abdalla, new species, and M. soleiana Abdalla & Deschodt, new species. Macroderes nitidus Harold, 1877 is redescribed and its lectotype is designated. The diagnostic characters as well as an updated geographic distribution of each species are summarised. An updated key of the genus, photographs of habitus, sclerites of internal sac, pronotum, pronotal punctures and elytra also are provided.